KUALITAS HADIS ETIKA UTANG PIUTANG - Nanang Lidwan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This research finds the qualities of ahÃ¢dits of debt in al-Kutub al-Sittah is accepted as hujja. There are researches about ahÃ¢dits of debt. They are: 1. Teungku Muhammad Hasbi Ash-Shiddieqy in his workâ€œKoleksi Hadis-Hadis Hukumâ€ (Semarang: Pustaka Rizki Putra, 2001). 2. Syamsul Rijal Hamid in his work â€œFatwa-fatwa Rasulullah 2: Seputar Masalah Transaksiâ€ (Jakarta: Cahaya Salam, 2001). This research will support previous reserches with some of result (qualities of transmittions). In assessment of each narrator, the writer tends to chose opinions of Ibn Hajar. and assessing the qualities of ahadÃ®ts, the writer employed the method of jarh wa ta'dil and he also saw opinions of moslem scholars of hadÃ®ts. In addition, the writer also dealt with the books of takhrÃ®j such as ShahÃ®h ahadÃ®ts, he refered to the sciences and critique of hadÃ®ts as the standard guidance of hadÃ®ts studies.